Using sticker to solve the 3-dimensional matching problem in molecular supercomputers. (8th August 2005) - Guo, Minyi; Chang, Weng-Long; Cao, Jiannong
Adleman demonstrated that DNA (Deoxyribonucleic acid) strands could be applied for dealing with solutions to an instance of the NP-complete Hamiltonian path problem (HPP) (Adleman, 1994). The Adleman techniques could also be used to solve the NP-complete satisfiability (SAT) problem (the first NP-complete problem) (Lipton, 1995). Furthermore, sticker is used for enhancing the Adleman-Lipton model (Roweis et al., 1999). In this paper, we first use sticker to construct solution space of DNA library sequences for the 3-dimensional matching problem. Then, in the Adleman-Lipton model, we propose an algorithm to remove illegal solution and find legal solution for the 3-dimensional matching problem from solution space of sticker. Finally, a simulation result for our algorithm is generated.